2004
DOI: 10.1038/nature03028
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free piezoceramics

Abstract: Lead has recently been expelled from many commercial applications and materials (for example, from solder, glass and pottery glaze) owing to concerns regarding its toxicity. Lead zirconium titanate (PZT) ceramics are high-performance piezoelectric materials, which are widely used in sensors, actuators and other electronic devices; they contain more than 60 weight per cent lead. Although there has been a concerted effort to develop lead-free piezoelectric ceramics, no effective alternative to PZT has yet been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
2,314
8
14

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 5,018 publications
(2,532 citation statements)
references
References 22 publications
25
2,314
8
14
Order By: Relevance
“…17b). This is supported by the XRD analysis (not shown): at room temperature the conventionally prepared KNLNT is orthorhombic, 306 whereas the mechanochemically prepared KNLNT could be indexed with the tetragonal structure, 295 in agreement with the original paper by Saito et al 274 The observed different T O-T (50 1C) in the conventionally processed KNLNT is probably related to the Ta inhomogeneities, e.g. incomplete incorporation of Ta into the solid solution and presence of Ta-poor(rich) regions with different T O-T (see Fig.…”
Section: àsupporting
confidence: 85%
See 1 more Smart Citation
“…17b). This is supported by the XRD analysis (not shown): at room temperature the conventionally prepared KNLNT is orthorhombic, 306 whereas the mechanochemically prepared KNLNT could be indexed with the tetragonal structure, 295 in agreement with the original paper by Saito et al 274 The observed different T O-T (50 1C) in the conventionally processed KNLNT is probably related to the Ta inhomogeneities, e.g. incomplete incorporation of Ta into the solid solution and presence of Ta-poor(rich) regions with different T O-T (see Fig.…”
Section: àsupporting
confidence: 85%
“…271,272 So far, the (K,Na)NbO 3 (KNN) solid solution has been one of the most studied among the alternatives. 273 The research on KNN was reinforced in 2004 by the paper of Saito et al, 274 who showed that piezoelectric properties comparable to PZT could be achieved by modifying KNN with Li, Ta and Sb, or by grain orientation (texturing). However, the high piezoelectricity of these materials originates from the enhanced polarizability associated with the compositional shift of the orthorhombicto-tetragonal polymorphic phase transition (PPT) from 195 1C for pure KNN 275 downward to room temperature.…”
Section: Other Oxidic Systemsmentioning
confidence: 99%
“…(1-x)(BaTiO3) 9 or x(NaNbO3). (1-x)(BaTiO3) 39 for potential high temperature capacitor applications. The method circumvents the issue of poor mixing of oxide or carbonate precursors in conventional mixed oxide routes, with starting materials being homogeneously distributed from the outset.…”
Section: Discussionmentioning
confidence: 99%
“…1 A leading candidate amongst a range of promising materials is the solid solution KNN (K x Na 1-x NbO 3 ). 2,3 Sodium niobate (NaNbO 3 ) itself is an intriguing material, with perhaps one of the most complex temperature-dependent phase diagrams amongst simple perovskites. 4 , 5 , 6 Although itself antiferroelectric (orthorhombic, Phase P, space group Pbcm) at ambient temperature, NaNbO 3 becomes ferroelectric (rhombohedral, Phase N, space group R3c, Glazer tilt system 7 a -a -a -) below 173 K. Depending on sample synthesis conditions, a ferroelectric polymorph, Phase Q (orthorhombic, space group P2 1 ma, Glazer tilt system a -b + a -) can co-exist with Phase P at room temperature.…”
Section: Introductionmentioning
confidence: 99%